Mobility Design: Die Zukunft der Mobilität gestaltenBand 2: Forschung (De Gruyter, 2022)
Climate change and the scarcity of resources, but also the steadily increasing amount of traffic, make it indispensable to develop new solutions for environmentally friendly and people-friendly mobility. With the expansion of digital information systems, we will in future be able to easily combine different modes of transport according to our needs. These developments are a great challenge for the design of different mobility spaces. While the focus in Volume 1 was on practice, Volume 2 now brings together research from the fields of design, architecture, urban planning, geography, social science, transport planning, psychology and communication technology. The current discussion about the traffic turnaround is expanded to include the perspective of user-centred mobility design.